Analisis Faktor Rasio Keuangan Sebagai Indikator Unqualified Opinion Pada BUMN Peraih Indonesia Good Corporate Governance Award 2017 - Muhammad Hasyim Ashari; Pudji Lestari (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to analyze the factors that underlie the auditor's considerations in providing an Unqualified Opinion on BUMN Tbk companies that won the Indonesia Good Corporate Governance Award 2017. This descriptive quantitative research uses exploratory factor analysis. The results of the study show that the financial ratios used as indicators in providing Unqualified Audit Opinions to BUMN Tbk companies that won the 2017 Indonesia Good Corporate Governance Award are the Liquidity Ratio and Solvency Ratio. The Liquidity Ratio used is the Current Ratio, Quick Ratio and Cash Ratio. Meanwhile, the Solvency Ratios used are Total Debt to Total Assets Ratio, Debt to Equity Ratio, Owner`s Equity to Total Assets Ratio, Owner`s Equity to Fixed Assets Ratio, Fixed Assets to Long Term Debt Ratio and Times Interest Earned Ratio. The indicators that are factors in giving the auditor's opinion are divided into 3 (three) main factors, namely the company's ability to fulfill its obligations both short and long term (Factor 1) is the main consideration of 65.383% in providing an Unqualified audit opinion, the balance factor of debt and equity (Factor 2) and the importance of the source of loan capital and the level of security owned by creditors (Factor 3) with a consideration value of 12.417% and 11.243%, respectively.